Promoting social change and democracy through information technology - Kumar, Vikas 1979- (Advances in electronic government, digital divide, and regional development (AEGDDRD) book series, 2015)
"This book is a definitive reference source for the latest scholarly research on the use of the internet, mobile phones, and other digital platforms for political discourse between citizens and governments"...